Epigenetic Signatures of Salivary Gland Inflammation in Sjögren's Syndrome. Issue 12 (December 2016) - Cole, Michael B.; Quach, Hong; Quach, Diana; Baker, Alice; Taylor, Kimberly E.; Barcellos, Lisa F.; Criswell, Lindsey A.
Abstract : Objective: Sjögren's syndrome (SS) is a complex multisystem autoimmune disease that results in progressive destruction of the exocrine glands. The purpose of this study was to characterize epigenetic changes in affected gland tissue and describe the relationship of these changes to known inflammatory processes. Methods: A genome‐wide DNA methylation study was performed on human labial salivary gland (LSG) biopsy samples obtained from 28 female members of the Sjögren's International Collaborative Clinical Alliance (SICCA) Registry. Gland tissue was methylotyped using the Illumina HumanMethylation450 BeadChip platform, followed by rigorous probe‐filtering and data‐normalization procedures. Results: A genome‐wide case–control study of 26 of the 28 subjects revealed 7, 820 differentially methylated positions (DMPs) associated with disease status, including 5, 699 hypomethylated and 2, 121 hypermethylated DMPs. Further analysis identified 57 genes that were enriched for DMPs in their respective promoters; many are involved in immune response, including 2 previously established SS genetic risk loci. Bioinformatics analysis highlighted an extended region of hypomethylation surrounding PSMB8 and TAP1, consistent with an increased frequency of antigen‐presenting cells in LSG tissue from the SS cases. Transcription factor motif enrichment analysis revealed the specific nature of the genome‐wide methylation differences, demonstrating colocalization of SS‐associated DMPs with stress‐ and immune response–related motifs. Conclusion: Our findings underscore the utility of CpG methylotyping as an independent probe of active disease processes in SS, offering unique insights into the composition of disease‐relevant tissue. Methylation profiling implicated several genes and pathways previously thought to be involved in disease‐related processes, as well as a number of new candidates.